2019
DOI: 10.1016/j.ajo.2018.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Anti-IL6-Receptor Tocilizumab in Refractory and Noninfectious Uveitic Cystoid Macular Edema: Multicenter Study of 25 Patients

Abstract: Cystoid macular edema (CME) is a leading cause of blindness. In this study we assessed the efficacy and safety of Tocilizumab (TCZ) in refractory CME. DESIGN: Retrospective case series. METHODS: Patients with CME secondary to non-infectious uveitis who had inadequate response to corticosteroids and at least one conventional immunosuppressive drug, and in most cases to other biological agents were studied. CME was defined as central retinal thickness greater than 300 µm. The primary outcome measure was macular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 39 publications
1
61
0
Order By: Relevance
“…Improve ments in anterior chamber cell counts and macular thickening were seen in retrospective studies of intra venous tocilizumab in juvenile idiopathic arthritis uveitis and adult uveitis, including adult juvenile idio pathic arthritis. [15][16][17][18] One study of tocilizumab in juvenile idiopathic arthritis used the juvenile idiopathic arthritis ACR pediatric 30 response at 12-16 weeks as the primary outcome, 20 which although not directly comparable to uveitis scores, are arguably a less robust response than a twostep decrease on the SUN inflammation score. Studies have also shown progressive improvements in uveitis activity 14 over 26 weeks and systemic juvenile idiopathic arthritis disease activity over 52 weeks 24 with tocilizumab.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Improve ments in anterior chamber cell counts and macular thickening were seen in retrospective studies of intra venous tocilizumab in juvenile idiopathic arthritis uveitis and adult uveitis, including adult juvenile idio pathic arthritis. [15][16][17][18] One study of tocilizumab in juvenile idiopathic arthritis used the juvenile idiopathic arthritis ACR pediatric 30 response at 12-16 weeks as the primary outcome, 20 which although not directly comparable to uveitis scores, are arguably a less robust response than a twostep decrease on the SUN inflammation score. Studies have also shown progressive improvements in uveitis activity 14 over 26 weeks and systemic juvenile idiopathic arthritis disease activity over 52 weeks 24 with tocilizumab.…”
Section: Resultsmentioning
confidence: 99%
“…In patients with severe disease that does not respond to methotrexate and antiTNF drugs, strong evidence sup ports the approach of targeting interleukin6 (IL6) in the disease pathogenesis. [14][15][16][17][18] Therefore, a phase 2 trial of the potential efficacy, safety, and tolerability of the IL6 receptor inhibitor tocilizumab was done. In arthritis, IL6 causes tiredness, anaemia, and inflammation, as well as dam age to bones, cartilage, and tissue; tocilizumab reduces these effects.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Additionally, TCZ in adults with non-anterior uveitis and refractory uveitis-related cystoid macula edema is well established. [14][15][16][17][18][19][20][21] The STOP-Uveitis Study demonstrated that monthly intravenous TCZ infusions significantly improved the visual, anatomic and inflammatory outcomes in patients with non-anterior uveitis with limited systemic and ocular adverse effects. 14 Comparable results were seen with sarilumab subcutaneous, another anti-IL-6 receptor, in adult uveitis.…”
Section: Discussionmentioning
confidence: 99%
“…22 Like in our study, corticosteroid-sparing effect of TCZ has been reported in many other studies. 14,15,17,18,[20][21][22] This is an important aspect since in our cohort, all patients had unwanted steroid-related complications i.e. growth retardation, Cushing syndrome and osteoporosis at this young age.…”
Section: Discussionmentioning
confidence: 99%
“…TCZ is also known to be effective in refractory inflammatory cystoid macular edema (CME) no matter its etiology. 121 Currently, few data support the use of TCZ in sarcoidosis. Preliminary data indicate that anti-IL-6 therapy could be an interesting therapeutic approach to treat multidrug-resistant sarcoidosis, but further studies must be carried out.…”
Section: Tocilizumabmentioning
confidence: 99%